Catering of high-risk foods and potential of stored food menu data for timely outbreak investigations in healthcare facilities, Italy and Germany. (22nd March 2023) - Boone, Idesbald; D'Errico, Michele Luca; Iannetti, Luigi; Scavia, Gaia; Tozzoli, Rosangela; Ethelberg, Steen; Eckmanns, Tim; Stark, Klaus; Wilking, Hendrik; Haller, Sebastian
Abstract: Healthcare-associated foodborne outbreaks (HA-FBOs) can cause significant morbidity and mortality, affecting particularly vulnerable hospital populations. Electronic records of food served in healthcare facilities (HCFs) could be useful for timely investigations of HA-FBOs. We explored the availability and usability of electronic food menu data to support investigations of HA-FBOs through a survey among 35 HCFs in Germany ( n = 13) and in Italy ( n = 22). Large variability was reported in the storage time of menu data (from no storage up to 10 years) and their formats, including paper, electronic (PDF, Word, Excel), or fully searchable databases (15/22 in Italian HCFs, 3/13 in German HCFs). Food products that may present a risk to vulnerable persons – including deli salads, raw/fermented sausage products, soft cheese, smoked fish or frozen berries – were offered on the menu of all HCFs in Germany, and one-third of the Italian HCFs. The usability of electronic food menu data for the prevention or investigation of HA-FBOs may be suboptimal in a large number of HCFs in Germany, as well as in some HCFs in Italy. Standardised collection for use of electronic food menu data might help discover the association between illnesses and food eaten during outbreak investigations. Hospital hygienists, food safety and public health authorities should collaborate to increase implementation of food safety guidelines.